'Le "je/jeu" intertextuel': textual interplay and intertextual identity in Roxanne Bouchard's Whisky et paraboles. Issue 2 (September 2015) - Bolfek-Radovani, Jasmina
<x content-type="archive" xml:space="preserve">Abstract</x> This article will offer an intertextual reading of Roxanne Bouchard's Whisky et paraboles by applying Julia Kristeva's theory of intertextuality, combined with the use of semiotic analysis. Bouchard's notion of an 'identité intertextuelle' will be introduced and discussed, followed by an analysis of the intertextual use of some of the main tropes in the text belonging to the genre of the roman de la terre and the Québécois nationalist novel. This interpretation allows for a reading of Roxanne Bouchard's novel that situates her text within but also outside the nationalist discourse and the paradigm of continuity which can be seen to characterise the Franco-Canadian and Québécois past and which forms part of the 'idéologie de la survivance', as advanced by Gérard Bouchard (2000). The article will argue that in Bouchard's novel intertextual identity and textual interplay operate in a dynamic space located between the paradigms of continuity and rupture. It will conclude that Roxanne Bouchard ultimately seeks to recover both the individual and collective past and cultural memory of Quebec in order to forge a new Québécois identity that is fully able to embrace and assume both its past and present.